2021
DOI: 10.1177/18681034211057569
|View full text |Cite
|
Sign up to set email alerts
|

The COVID-19 Pandemic and the Emergence of Vietnam as a Middle Power

Abstract: Limited capability and political will have caused the great powers to fail to demonstrate their global leadership in the fight against the COVID-19 pandemic, which has created greater room to manoeuvre for other countries to influence international affairs. Preliminary achievements in the fight against the COVID-19 crisis have buttressed the rising global status of small and medium-sized states, including Vietnam. Although Vietnam has recently been recognised as an emerging middle power, scepticism looms regar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 25 publications
(30 reference statements)
0
2
0
Order By: Relevance
“…This demonstrated that adults' perceived ability and ease of receiving a COVID-19 vaccine significantly contribute to their COVID-19 vaccination intention. At the time of this study, even though the COVID-19 vaccines were not available for over 100 million Vietnamese citizens, many individuals could easily access COVID-19 vaccines as Vietnam received support from the international community thanks to the success of the COVID-19 vaccine diplomacy policy [ 12 , 70 ]. From our participants, 890 of the 2722 adults had already received at least one dose of the vaccine.…”
Section: Discussionmentioning
confidence: 99%
“…This demonstrated that adults' perceived ability and ease of receiving a COVID-19 vaccine significantly contribute to their COVID-19 vaccination intention. At the time of this study, even though the COVID-19 vaccines were not available for over 100 million Vietnamese citizens, many individuals could easily access COVID-19 vaccines as Vietnam received support from the international community thanks to the success of the COVID-19 vaccine diplomacy policy [ 12 , 70 ]. From our participants, 890 of the 2722 adults had already received at least one dose of the vaccine.…”
Section: Discussionmentioning
confidence: 99%
“…Still, local scholars have been resorting to it lately in an increasingly active manner, developing this framework more or less independently. This resulted in a number of publications (mostly by the DAV), including, for instance, the relevance of this concept in the COVID-19 pandemic [Le Dinh Tinh, Vu Thi Thu Ngan 2021]. Notwithstanding the argument as to whether Vietnam is still on the way in its quest to become a middle power (supported i.a.…”
Section: Resultsmentioning
confidence: 99%
“…It would be inaccurate, however, to assume that the philosophy of bamboo diplomacy is an entirely novel phenomenon in Vietnamese strategic thinking. Instead, the conceptualization of bamboo diplomacy resembles a natural evolution and accumulation of previous and ongoing policies (Do, 2017(Do, , 2022Le and Vu, 2022).…”
Section: The Leadership Role Of the Vcp In Vietnam's Modern Foreign P...mentioning
confidence: 99%